PROTECTION AND PROTECTION OF INTELLECTUAL PROPERTY RIGHTS - Estayev Абзал Куанышбекович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
отсутствует